STUDY OF ART AND NATURALSCIENCE: THE MODERN POSIBILITY OF COOPERATION - Кунденко, Я. Н.; Старикова, Г. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article is devoted to the problem of using the methodology to the investigation of the work of art. Especially the possibilities and the limits of using the synergetic methodology and the theory of fractals for studying the art artifacts was analyzed in the article.